(untitled) (Construction Economics and Building, 2015)
Leadership and Sustainability in the Built Environment Opoku, A. and Ahmed, V. (ed.), 2015. Leadership and Sustainability in the Built Environment. Routledge, London. ISBN (hbk): 978-1-13-877842-9, Hardback: 155.00.